1982
DOI: 10.1063/1.442757
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and triplet state lifetime for yttrium fluoride (YF) in inert gas matrices

Abstract: Absorption and emission spectra are reported for YF isolated in Ne, Ar, and Kr matrices and the ground state is confirmed as 1Σ+. Calculated Franck–Condon intensities permit confident assignments of vibrational quantum numbers for most of the states but point to an anomaly in the red emission produced on excitation into the B̃ state. Lifetime studies in argon show that such excitation also depletes ∼90% of the ground state population and that the return requires ∼15 min. As explanation, the ã 3Δ state of YF is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The ~ = 1-X 1E band is probably identical to the absorption band at 24 100cm-~ observed for YF isolated in an argon matrix [7]. Now, the only unknown low-lying state is the A IA state.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The ~ = 1-X 1E band is probably identical to the absorption band at 24 100cm-~ observed for YF isolated in an argon matrix [7]. Now, the only unknown low-lying state is the A IA state.…”
Section: Discussionsupporting
confidence: 65%
“…The interpretation of the infrared fluorescence spectra of the matrix isolated YF molecule [7] is apparently erroneous. The Kr + line excites a high vibrational level of the baH state rather than a level of the high-lying 3~ state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10][11] Low temperature matrix isolation studies have been performed 12,13 and theoretical investigations [14][15][16] have confirmed that these molecules exhibit a ground state symmetry of 1 ⌺ + , correlating to the M + ͑ns 2 ͒F − ͑3s 2 3p 6 ͒ ͑M = Sc, Y, or La͒ electronic configuration. High temperature thermal emission and laser spectroscopic investigations on these molecules have revealed several singlet-singlet and triplet-triplet transitions that have been rotationally analyzed, and spectroscopic constants have been determined.…”
Section: Introductionmentioning
confidence: 99%